Acute-on-Chronic Liver Failure: Pathophysiological Mechanisms and Management - Khanam, Arshi; Kottilil, Shyam (Frontiers in Medicine, 2021)
Acute-on-chronic liver failure (ACLF) is a multifaceted condition with poor treatment options and high short-term mortality. ACLF can develop in patients with or without liver cirrhosis, where patients with decompensated cirrhosis display higher risk of short-term mortality. Pathophysiological mechanisms include systemic inflammation due to bacterial and fungal infections and acute hepatic insult with drug, alcohol and viral hepatitis. Cryptogenic factors also contribute to the development of ACLF. The clinical outcome of ACLF patients gets further complicated by the occurrence of variceal hemorrhage, hepatorenal syndrome, hepatic encephalopathy and systemic immune dysfunction. Regardless of the better understanding of pathophysiological mechanisms, no specific and definitive treatment is available except for liver transplantation. Recent approach of regenerative medicine using mesenchymal stem cells (MSCs) could be advantageous for the treatment of ACLF as these cells can downregulate inflammatory response by inducing anti-inflammatory events and prevent hepatic damage and fibrosis by inhibiting hepatic stellate cell activation and collagen synthesis. Moreover, MSCs are involved in tissue repair by the process of liver regeneration. Considering the broad therapeutic potential of MSCs, it can serve as an alternative treatment to liver transplant in the near future, if promising results are achieved.